Testing validity of observed indicators of local content policy in Nigeria: evidence from four-factor measurement model - Adedeji, Abdulkabir N.; Lawan, Muhammad O.; Sidique, Shaufique F. (Central Bank of Nigeria, 2017)
This paper tests validity property of the indicators that measured local content policy (LCP) in Nigeria’s oil sector. Survey data were obtained for the test, using confirmatory factor analysis (CFA) method. The results obtained from a four-factor measurement model confirmed the LCP indicators to be valid. This reflects that the policy can achieve its developmental targets on local value creation with particular reference to increased local firms’ participation, backward linkages, and job creation in Nigeria’s oil sector. Hence, government should focus on effective implementation and compliance of the policy rather than “labour clause” as contained in the local content Act. However, government should be aware of the trade-off that the policy may entail.